Influence of compression ratio on the performance characteristics of a spark ignition engine - A. Raji, Nurudeen; O. Kuku, Rafiu; O. Openibo, Adeshola; A. Owolabi, Emmanuel (Journal of Production Engineering, 2024)
In this study, the influence of the compression ratio on the performance characteristics of a gasoline engine was investigated in detail using COMSOL simulations. Four compression ratios — 8, 9, 10 and 11 — were investigated at different engine speeds between 1000 and 1800. The analysis focused on power output, braking performance and fuel consumption in order to decipher the complicated relationships between compression ratios and engine dynamics. The results showed a significant increase in power output with increasing compression ratio, highlighting the delicate balance required for optimal power generation. Braking power increased with higher compression ratios, indicating a potential improvement in braking performance. In addition, the study showed a correlation between increased fuel consumption and higher compression ratios, highlighting the need for strategic fuel-saving measures. These results contribute to the understanding of gasoline engine behavior and provide insights into the trade-offs that need to be made when adjusting the compression ratio. Recommendations include experimental validation, exploration of dynamic compression control, research into integrated braking systems, investigation of sustainable fuel strategies and a focus on multi-metric optimization. The observed increase in power output at higher compression ratios highlights an important aspect of engine optimization. Engineers and researchers need to carefully consider compression ratio adjustments to ensure optimal power generation while maintaining efficiency. This insight can guide the development of engines that strike an ideal balance between power and fuel efficiency.